SOLITARY WAVES ON A CRUSTAL FAULT - Bykov V.G. (My University, 2001)
A microphysical model is proposed for deformation of granular materials to describe time-dependent slip on a fault, resulting in a "perturbed" sine-Gordon equation. The fault walls interact by friction during relative displacement, the friction being simulated by introducing an effective viscosity of a crushed geomaterial in the fault zone. An exact analytical solution in the form of a solitary wave can be derived, when it is assumed that roughness grains are distributed in a periodic manner along the fault and that the drag exerted by the grain contact surfaces is proportional to the square of shear flow velocity in the parting between the fault surfaces. The dynamical parameters of slow steady slip and rapid failure-causing slip found from the model are in agreement with the observation data.